Heat detector alarm system / Sharifah Norziah Sayed Mohamed Zain, Siti Norshahirah Abdullah and Siti Nur Anis Zakaria - Sayed Mohamed Zain, Sharifah Norziah; Abdullah, Siti Norshahirah; Zakaria, Siti Nur Anis (2015)
This project is designed to notify the building occupant to evacuate to the safer area as soon as fire detected which call the heat detector alarm system. This heat detector alarm system has three subsystems which are the detecting system, warning system and controlling system. The overall system of heat detector alarm system is controlled by the Arduino. The detection system operates as the fire detector. In this detection system, LM35 acts as the main sensor which is to detect the surrounding temperature. The sensor is placed at the control room in the building and the LCD used to display the current temperature and the current condition. The buzzer is in the warning system while the water sprinkler motor for the controlling system. Once the detected temperature above than 45°C, the buzzer and the LED act as the guide path to the safer area will on simultaneously while the water motor will active after ten second the LED and buzzer on